Efficacy, pharmacokinetics, and safety of the biosimilar CT-P10 in comparison with rituximab in patients with previously untreated low-tumour-burden follicular lymphoma: a randomised, double-blind, parallel-group, phase 3 trial - Ogura, Michinori; Sancho, Juan Manuel; Cho, Seok-Goo; Nakazawa, Hideyuki; Suzumiya, Junji; Tumyan, Gayane; Kim, Jin Seok; Lennard, Anne; Mariz, José; Ilyin, Nikolai; Jurczak, Wojciech; Lopez Martinez, Aurelio; et al. (The Lancet. Haematology, 2018)
BACKGROUND: Studies in patients with rheumatoid arthritis and advanced follicular lymphoma have shown that CT-P10, a rituximab biosimilar, has equivalent or non-inferior efficacy and pharmacokinetics to rituximab. We aimed to assess the therapeutic equivalence of single-agent CT-P10 and rituximab in patients with newly diagnosed low-tumour burden follicular lymphoma. METHODS: In this ongoing, randomised, double-blind, parallel-group, active-controlled, phase 3 trial, adult patients (≥18 years) with stage II-IV low-tumour-burden follicular lymphoma were randomly assigned (1:1) using an interactive web or voice response system stratified by region, stage, and age to CT-P10 or US-sourced rituximab. Patients received CT-P10 or rituximab (375 mg/m2 intravenous) on day 1 of four 7-day cycles (induction period). Patients who had disease control after the induction period continued to a maintenance period of CT-P10 or rituximab administered every 8 weeks for six cycles and, if completed, a second year of maintenance therapy of additional CT-P10 (every 8 weeks for six cycles) was offered. The study was partially unmasked after database lock (Feb 23, 2018) for all data up to 7 months (before cycle 3 of the maintenance period). The primary endpoint was the proportion of patients who achieved an overall response by 7 months in the intention-to-treat population. Efficacy equivalence was shown if the two-sided 90% CIs for the treatment difference in the proportion of responders between CT-P10 and rituximab was within the equivalence margin of 17%. This trial is registered with ClinicalTrials.gov, number NCT02260804. FINDINGS: Between Nov 9, 2015, and Jan 4, 2018, 402 patients were assessed for eligibility, of whom 258 were randomly assigned: 130 to CT-P10 and 128 to rituximab. 108 (83%) of 130 patients assigned to CT-P10 and 104 (81%) of 128 assigned to rituximab achieved an overall response by month 7 (treatment difference estimate 1·8%; 90% CI -6·43 to 10·20). Therapeutic equivalence was shown (90% CIs were within the prespecified margin of 17%). The most common grade 3 or 4 treatment-emergent adverse events were decreased neutrophil count (two grade 3 in the CT-P10 group) and neutropenia (one in each group); all other grade 3 or 4 treatment-emergent adverse events occurred in one patient each. Six (5%) of 130 patients who received CT-P10 and three (2%) of 128 who received rituximab experienced at least one treatment-emergent serious adverse event. INTERPRETATION: CT-P10 was equivalent to rituximab in terms of efficacy and was well tolerated. CT-P10 monotherapy is suggested as a new therapeutic option for patients with low-tumour-burden follicular lymphoma. FUNDING: Celltrion, Inc.
Keywords: dvojitá slepá metoda; Treatment Outcome; folikulární lymfom; Female; Humans; Safety; tumor burden; přežití bez známek nemoci; biosimilární léčivé přípravky; lidé středního věku; výsledek terapie; bezpečnost; myší monoklonální protilátky; Rituximab; Lymphoma, Follicular; Disease-Free Survival; Antibodies, Monoclonal, Murine-Derived; lidé; mužské pohlaví; Tumor Burden; Double-Blind Method; rituximab; Male; ženské pohlaví; Biosimilar Pharmaceuticals; Middle Aged